The Erosion of Autonomy in Online Consumer Transactions - MIK, Eliza (Institutional Knowledge at Singapore Management University, 2016)
Online businesses influence consumer behaviour by means of a wide range of technologies that determine what information is displayed as well as how and when it is displayed. This creates an unprecedented power imbalance between the transacting parties, raising questions not only about the permissible levels of procedural exploitation in contract law, together with the adequacy of existing consumer protections but also about the impact of technology on consumer autonomy. There is, however, no single technology that threatens the latter. It is the combined, mutually-enforcing effect of multiple technologies that influence consumer choices at different stages in the transacting process, creating an environment of ambient and pervasive manipulation. It starts the moment consumers enter a search term (autocomplete), proceeds through the display of search results (search engine bias), the speed with which a website appears on the screen (traffic management) and concludes with the layout of elements on a website (interface design), to name a few.